Risk estimation for familial breast cancer: improving the system of counselling. - Gregory, H; Wordsworth, S; Gibbons, B; Wilson, B; Haites, N (2007)
Women with a family history of breast cancer dominate referrals for cancer genetic risk counselling across Europe. Given limited health care resources, managing this demand, while achieving good value for money for health services, is a major challenge. The paper reports the benefits and associated costs of moving from a traditional system of deriving family history of cancer during the patient's initial clinic attendance, to a protocol-driven system with pre-counselling assessment of family history. The evaluation was based on retrospective clinical data and a clinical audit. Changes in risk between referral and final risk assessment were ascertained and the cost difference between the two systems estimated. The study results showed that 14% of women assessed as 'low' genetic risk at referral were reassessed as 'moderate' or 'high' genetic risk for breast cancer following verification of family history. Sixteen per cent of those assessed as 'moderate' or 'high' genetic risk at referral were reassessed as 'low' genetic risk for breast cancer. Compared to the traditional system, the new protocol-driven system of risk assessment was more consistent, which reduced the number of return appointments and created time for clinicians to spend with other patients. The estimated cost of family history verification and genetic clinic appointment was calculated as 91.68 pounds (132.53 euro) per family history, compared to 104.00 pounds (150.34 euro) for the traditional system, representing a slight reduction in health service costs. Finally, the protocol-driven system can be used as part of ongoing audit for planning future genetics services in Scotland.